2017
DOI: 10.14474/ptrs.2017.6.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of self-myofascial release on hamstring flexibility

Abstract: Objective: This study aimed to identify the area with greatest effect using self-myofascial release technique (self-MFR) in the hamstring, suboccipital, and plantar regions. Design: Cross-sectional study. Methods: Twenty-two adult subjects were evaluated for flexibility and hamstring pain threshold after self-MFR. Based on the superficial back line, the self-MFR application areas were the suboccipital region, hamstring, and plantar regions. Self-MFR was applied to each area using a wooden pole for a total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…In addition, these findings are similar to those reported by Schroeder et al (2019) who showed an increase of 30.26% when a foam roller protocol was applied on paraspinal and lateral back muscles in healthy young females. Although several authors show flexibility improvements after foam roller application in a fatigued state, considerable variability in the results obtained on lumbar spine flexibility improvements have been reported (Grieve et al, 2015; Jung et al, 2017; Rey et al, 2019; Schroeder et al, 2019). Protocol variations could be responsible for the differences in findings which include pressure exerted by the roller, duration of intervention and speed of application (Dębski, Białas & Gnat, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these findings are similar to those reported by Schroeder et al (2019) who showed an increase of 30.26% when a foam roller protocol was applied on paraspinal and lateral back muscles in healthy young females. Although several authors show flexibility improvements after foam roller application in a fatigued state, considerable variability in the results obtained on lumbar spine flexibility improvements have been reported (Grieve et al, 2015; Jung et al, 2017; Rey et al, 2019; Schroeder et al, 2019). Protocol variations could be responsible for the differences in findings which include pressure exerted by the roller, duration of intervention and speed of application (Dębski, Białas & Gnat, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The initial literature search yielded a total of 29,964 citations, from which 196 were included for further reading. After review of full texts, 188 studies were excluded leaving 8 eligible randomized controlled studies [13][14][15][16][17][18][19][20] to be included in the review. Figure 1 shows the QUORUM flow diagram, summarizing the selection process and the number of studies excluded at each stage with reasons.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In terms of the number of rolling periods in one session, the studies can be divided into two groups. The first is made up of studies in which the authors used a single rolling set [8,10,16,19,22,24,29,33,38,45,53,55,57,59,68,69,73]. In the other studies, the values 2, 3, 4 and 5 appeared with similar frequency, with three rolling sets being the most commonly chosen option [3,5,15,23,26,35,39,46,57,62].…”
Section: Number Of Applications In One Treatment Sessionmentioning
confidence: 99%
“…As many as 41 authors carried out their studies in one treatment session. In the remaining studies, two [47,48,68] or three [15,33,37,38,57] treatment sessions were used as well. Seven researchers used a longer protocol.…”
Section: Number Of Treatment Sessionsmentioning
confidence: 99%